2020
DOI: 10.1007/s11557-020-01564-w
|View full text |Cite
|
Sign up to set email alerts
|

Two new species in a new genus and a critical revision of Brachybasidiaceae (Exobasidiales, Basidiomycota) in honor of Franz Oberwinkler

Abstract: The Brachybasidiaceae are a family of 22 known species of plant-parasitic microfungi belonging to Exobasidiales, Basidiomycota. Within this family, species of the largest genus Kordyana develop balls of basidia on top of stomatal openings. Basidial cells originate from fungal stroma filling substomatal chambers. Species of Kordyana typically infect species of Commelinaceae. During fieldwork in the neotropics, fungi morphologically similar to Kordyana spp. were found on Goeppertia spp. (syn. Calathea spp., Mara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…Several species of Kordyana, in particular K. brasiliensis, K. tradescantiae, and K. celebensis, are considered promising candidates for biocontrol of invasive weeds, such as Tradescantia fluminensis in Australia, New Zealand, and China and C. benghalensis in the United States and China [4][5][6]. Although Kordyana is the oldest genus in Brachybasidiaceae, knowledge at the genus and species level is still incomplete owing to taxonomic problems and the lack of morphological descriptions and DNA sequencing for some species [7]. In this study, we identified and described a species of Kordyana, newly found on C. communis and C. minor, based on morphological characteristics and molecular phylogenetic analyses.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Several species of Kordyana, in particular K. brasiliensis, K. tradescantiae, and K. celebensis, are considered promising candidates for biocontrol of invasive weeds, such as Tradescantia fluminensis in Australia, New Zealand, and China and C. benghalensis in the United States and China [4][5][6]. Although Kordyana is the oldest genus in Brachybasidiaceae, knowledge at the genus and species level is still incomplete owing to taxonomic problems and the lack of morphological descriptions and DNA sequencing for some species [7]. In this study, we identified and described a species of Kordyana, newly found on C. communis and C. minor, based on morphological characteristics and molecular phylogenetic analyses.…”
mentioning
confidence: 99%
“…Rhamphospora nymphaeae (GenBank accession nos. NR119615 and NG057757) was used as an outgroup taxon per the phylogenetic results of Piepenbring et al [7]. Two phylogenetic trees were constructed for the sequences of both the ITS and LSU regions using MEGA7 software [11] based on neighbor-joining (NJ) analysis with the following conditions: gaps in the sequence alignment were treated as deletions, evolutionary distances were calculated using the Kimura-2-parameter model, including substitutions of transitions and transversions, and bootstrap values for branches were calculated using one thousand replicates.…”
mentioning
confidence: 99%
See 3 more Smart Citations